Test-retest Reliability of the Fear COVID-19 Scale: A Pilot Study - Henny Dwi Susanti, M.Kep., Sp. Kep. Mat; Ismaila Sonko; Andi Muhammad Yaurie; Indah Dwi Pratiwi; Edi Purwanto; Henik Tri Rahayu; Faqih Ruhyanuddin (University of Muhammadiyah Malang, 2022)
Introduction: the context of the study The new coronavirus COVID-19 is a pandemic disease that currently attacks all countries, including Indonesia, where the number of people who have died in 7.169 cases and those confirmed positive are 165.887 cases. The increasing number of COVID-19 cases in Indonesia has heightened the anxiety and fear experienced by everyone. Objectives: The main objective of this study is to analyze the psychometric properties of the Indonesian translation version of the COVID-19 Fear Scale (FCV-19S) using a sample population in Indonesia. Methods: This study is a cross-sectional instrumental study. The method in this study uses the convenience sampling method. Results: This result showed good internal consistency with the value of Cronbach’s alpha was 0.87. Conclusion: This study indicated good internal consistency. Future research is to evaluate the correlation between other variables. This study could be applied to the Indonesian population to screen fear of Covid-19 during the pandemic.